Adverse childhood experiences and spiritual well-being among Turkish people: A serial mediation through meaningful living and death obsession - Kurtulus, Hacer Yildirim; Satici, Seydi Ahmet; Deniz, M. Engin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Negative experiences such as neglect and abuse experienced in childhood are important in the development of lifelong mental health problems and shaping well-being. Therefore, examining the lifetime impact of adverse childhood experiences (ACEs) to investigate mechanisms that will enhance well-being is an important task. This study investigated the effect of adverse childhood experiences on spiritual well-being and the serial mediating role of meaningful living and death obsession in this relationship. The study sample consists of a total of 389 volunteering Turkish participants, including 306 women (78.7%) and 83 men (21.3%). The participants' ages range from 18 to 60 (M = 25.56 years, SD = 10.22). The research employs a cross-sectional descriptive design based on structural equation modeling. In addition to structural equation modeling, bootstrapping analysis was also conducted. The results of the study suggest that the relationship between ACEs and spiritual well-being is serially mediated by meaningful living and death obsession (beta = - 0.039, 95% CI = - 0.074, - 0.018; p < .01). This study examined the indirect rather than direct effects of ACEs on spiritual well-being. In this context, it is assumed that ACEs affect spiritual well-being through meaning in life and preoccupation with death.
Keywords: Adverse childhood experiences; meaningful living; death obsession; spiritual well-being; Turkey; SELF-ESTEEM; LIFE; MALTREATMENT; ADULTS; RELIGIOSITY; SYMPTOMS; DISTRESS; VALIDITY; CULTURE; ANXIETY; Religion